PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS - Mulyaningsih, Sri; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is conducted to test the influence of cash turnover, account receivable turnover and inventory turnover to the profitability on food and beverages companies which are listed in Indonesia Stock Exchange (IDX) in the 2009-2013 periods. The cash turnover, account receivable turnover, and inventory turnover are the independent variables. Meanwhile, the profitability is the dependent variable. The samples are food and beverages companies which are listed in Indonesia Stock Exchange (IDX) in the 2009-2013 periods. The sample collection method has been done by using purposive sampling method and 8 companies have been selected as samples. The multiple linear regressions are used as the analysis method.The result of this research shows that significantly cash turnover has influence to the profitability whereas the account receivable turnover and inventory turnover do not have any influence to the profitability. The value of adjusted R square is 0.251 which shows that 25.1% of ROA can be explained by the independent variables i.e.: cash turnover, account receivable turnover, and inventory turnover whereas the remaining is explained by the other variables outside this research.  Keywords:            Return on Assets, Cash Turnover, Account Receivable Turnover and Inventory Turnover.